Biosocial predictors and blood pressure goal attainment among postmenopausal women with hypertension - Geetha Kandasamy; Thangamani Subramani; Gigi Sam; Mona Almanasef; Tahani Almeleebia; Eman Shorog; Asma M. Alshahrani; Amjad Hmlan; Atheer Y. Al Suhaym; Kousalya Prabahar; Vinoth Prabhu Veeramani; Palanisamy Amirthalingam (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesIn postmenopausal states, women may not maintain blood pressure (BP) in the same way as men, even though most women follow their treatment plans and prescriptions more consistently than men. Biological and lifestyle factors influence the progression of hypertension in postmenopausal women (PMW). This study aimed to determine biosocial predictors associated with achieving the target BP in PMW with hypertension.MethodsA prospective observational study was conducted in the General Medicine Department at Karuna Medical College Hospital, Kerala, India. The definition of BP goal attainment was established based on the guidelines outlined by the VIII Joint National Committee 2014 (JNC VIII). Multivariate logistic regression analysis was used to analyse biosocial predictors, such as educational status, employment status, body mass index (BMI), number of children, age at menarche, age at menopause, and number of co-morbidities, associated with BP goal achievement.ResultsOf the patients, 56.4% achieved their BP goals on monotherapy and 59.7% achieved it on combination therapy. Level of education [odds ratio (OR) = 1.275, 95% confidence interval (CI): 0.234–7.172], employment status (OR = 0.853, 95% CI: 0.400–1.819), age at menopause (OR = 1.106, 95% CI: 0.881–1.149), number of children (OR = 1.152, 95% CI: 0.771–1.720), BMI (OR = 0.998, 95% CI: 0.929–1.071), and number of co-morbidities (OR = 0.068, 95% CI: 0.088–1.093) did not show a significant relationship, and age at menarche (OR = 1.577, 95% CI: 1.031–2.412) showed a significant association with BP goal attainment among hypertensive postmenopausal women.ConclusionHalf of the hypertensive postmenopausal women did not achieve their BP goals. Interventions are required to expand screening coverage and, under the direction of medical professionals, there should be plans to improve hypertension control and increase awareness of the condition.